Behavior Disorders Prevalence in High School Students in Hamedan Province - Ali Reza Zolfaghari; Davoud Fathi; Omid Massah (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Behavioral disorders of childhood and adolescence represent a range of problems and Its prevalence varies in different parts of Iran and the world. Knowledge of them is essential to the prevention, treatment and rehabilitation of patients. The aim of this survey is assessment of behavior disorders prevalence in high school students in Hamedan province. Materials & Methods: In this descriptive and cross sectional study, 500 boy and girl students were selected from Hamedan high schools by multistep cluster sampling, based on region and gender. Data were gathered by Achenbach experience questionnaire (YSR form) and analyzed by Friedman and independent T tests. Results: The findings showed that prevalence of behavioral problems among students in the province is 10 percent and it was higher in girls than boys. Most disorders were withdrawal disorder / anxiety and attention problems and somatization disorder was the least problem. Conclusion: Prevalence of behavior disorders in Hamedan province compared to other studies is moderate, but the behavior disorders prevalence of boys and girls are different from other researchs.